Optimal Control for the Target-Tracking Problem using Three-Axis Camera Gimbals - Do, Dang Khoa; Le, Quang Duong (Old Journal, 2018)
In this paper, the target-tracking problem of a 3-axis camera gimbal mounted on a flying vehicle is considered. In order to keep the camera’s line of sight continuously pointing to a moving target, an optimal controller using LQR control techniques is applied. The motion equations of the gimbal system are derived by the Lagrangian approach considering the vehicle motion. The LQR controller is designed based on the system’s continuously linearized model. A tuning method for the LQR is also proposed to make the gimbal system point to a moving target in the shortest time. The feasibility of the proposed controller is shown by numerical simulations.